The Creative Techniques in Teaching Vocabulary at Sabilussalam Kindergarten Surabaya - Wijayanti -; Amrin Batubara; Gusti Nur Hafifah (Tell : Teaching of English Language and Literature Journal, 2014)
This research is conducted to find out the creative techniques, the implementation, and the advantages of the implementation of the creative techniques in teaching vocabulary at Sabilussalam kindergarten where pupils level B and 1 teacher are as subject. While, the objects of the research is all information related to the creative techniques in teaching vocabulary at Sabilussalam kindergarten.This research usesdescriptive qualitative method and the data collection techniques are classroom observations, documentation and interview. For analyzing the data, the researcher uses interactive model which is adapted from Miles and Hubberman (19984:6). The finding showedthat there are four creative techniques in teaching vocabulary at Sabilussalam kindergarten. Those were, Sing song, Drilling, Role play, and Game techniques. Besides, the researcher found theteaching techniques were implemented creatively in different ways. Firstly, the drilling technique was implemented by using gestures, and hip hop style. Secondly, the singing song technique was implemented by using gestures, repetitions, hip-hop and sound of clap the table. Thirdly, the role play was implemented by usingthe performing robot’s actions, super hero and play Dora’s adventure. Finally, the Game technique was implemented by using whispers, gestures, robot’s movements and guess. Additionally, all of implementations of the creative techniques in teaching vocabulary at Sabilussalam have some advantages. They are to develop children’s knowledge, skills, understanding and attitudes. The techniques can develop their knowledge because it can help them to improve their vocabulary in meaning and understanding. Besides, they can develop their skill because these techniques not only help them to improve their vocabulary but also explored in their skill especially the listening and the speaking skill which werethe basic skill had been mastered for young learner. Additionally, the techniques can develop children’s understanding and attitude because they were not only know and memorized vocabulary which had been taught but also they can understand the meaning word and explored their idea, expression in their daily activity.